Aggregate uncertainty, political instability and redistribution - Giorgio Bellettini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1995)
This paper associates political instability to real shocks affecting the income of the median voter, in a two-period model where two political parties set redistribution in order to defend the interests of well-dened constituencies. Implemented policies affect future voting outcomes and an intertemporal trade-off arises for the parties since their optimal one-period strategy does not maximize the probability of being reelected. The higher the volatility of the real shock, the more likely that parties deviate from the optimal one-period strategy by choosing a conservative strategy, which increases their chances of reelection and the expected lifetime utility of their constituencies.
Keywords: 330